Factors associated with health-related quality of life in gynaecologic cancer survivors with lower limb lymphedema: a cross-sectional study in Taiwan - Kuei-An Cho; Ming-Huei Cheng; Whei-Mei Shih; Shu-Ching Chen (BMC, 2023)
Abstract Backgrounds Gynaecological cancer survivors may develop lower limb lymphoedema after surgery, which negatively impacts quality of life. The purposes of this study were (1) to assess the levels of symptom distress, depression, body image, and health-related quality of life (HRQoL); (2) to recognize factors associated with HRQoL related in gynaecologic cancer survivors with lower limb lymphoedema. Methods A cross-sectional study was conducted with convenience sampling of gynaecologic cancer survivors with lower limb lymphoedema. Gynaecologic cancer survivors were assessed for symptom distress, depression, body image, and HRQoL. Multiple regression analysis was conducted to recognize the factors associated with HRQoL. Independent-samples t-test was used to compare symptom distress, depression, body image, and HRQoL by grade of lymphoedema. Results The most common distressing symptoms of lower limb lymphoedema were lower extremity oedema, lower extremity tightness, and lower extremity stiffness. Worse HRQoL was associated with more symptom distress, less satisfaction with body image, a high grade of lymphoedema, and a longer duration of lower limb lymphoedema. These factors explained 76.5% of the variance in HRQoL. Gynaecologic cancer survivors with late grade lymphoedema experienced lower HRQoL and higher levels of symptom distress, depression, and greater dissatisfaction with body image than those who had early grade lymphoedema. Conclusions Symptom distress had the strongest association with overall HRQoL and with all individual domains of HRQoL, except mental function. These results suggest that educating gynaecologic cancer survivors to assess lower limb lymphoedema-related problems, providing symptom management, and guiding survivors in physical activity to relieve lower extremity discomfort can improve HRQoL.